Three-dimensional mathematical model of a high temperature polymer electrolyte membrane fuel cell - Hess, Victor George (Department of Mathematics and Applied Mathematics, 2017)
Polymer electrolyte fuel cells are regarded as one of the most promising alternatives to the depleting and high pollutant fossil fuel energy sources. High temperature Polymer electrolyte fuel cells are especially suitable for stationary power applications. However, the length scale of a PEM fuel cells main components range from the micro over the meso to the macro level, and the time scales of various transport processes range from milliseconds up to a few hours. This combination of various spatial and temporal scales makes it extremely challenging to conduct in-situ measurements or other observations through experimental means. Thus, numerical simulation becomes a very important tool to help understand the underlying electrochemical dynamics and transient transport phenomena within PEM fuel cells. In this thesis research a comprehensive, three- dimensional mathematical model is developed which accounts for the convective and diffusive gas flow in the gas channel, multi-component diffusion in the porous backing layer, electrochemical reactions in the catalyst layers, as well as flow of charge and heat through the solid media. The governing equations which mathematically describe these transport processes, are discretized and solved using the finite-volume based software, Ansys FLUENT, with its in-built CFD-solvers. To handle the significant non-linearity stemming from these transport phenomena, a set of numerical under-relaxation schemes are developed using the programming language C++. Good convergence is achieved with these schemes, though the model is based on a serpentine single-channel flow approach. The model results are validated against experimental results and good agreement is achieved. The result shows that the activation overpotential is the greatest cause of voltage loss in a high temperature PEM fuel cell. The degree of oxygen depletion in the catalyst layer, under the ribs, is identified and quantified for a given set of input parameters. This factor is followed by membrane resistance to protonic migration. The model can thus be suitable applied as a tool to predict cell performance. The results also show that performance is influenced by not just one, but a combination of inter-related factors, thus temperature increases, and flow rate changes will only be effective if simultaneously, the concentration of inlet oxygen, and the mobility of proton-ions in the membrane is increased. Not only does the model results verify these phenomena, but provide a quantitative output for any given set of input parameters. It can therefore be suitably applied as an optimisation tool in high temperature PEM fuel cell design.